Gangrenous mastitis in sheep caused by multidrug-resistant Staphylococcus haemolyticus - Guilherme S. Moura; Rinaldo A. Mota; Michele F.S. Marques; Atzel C.A. Abad; Luciana B.B.C. Costa; Fernando N. Souza; Valdir M. Almeida; Givaldo B. Silva Filho; Hisadora A.S.C. Bom; Francine Klaumann; Francisco A.L. Souza; Fábio S. Mendonça (Pesquisa Veterinária Brasileira, 2021)
ABSTRACT: Mastitis is a multifactorial disease and considered one of the most critical problems in the dairy industry worldwide. The condition is characterized by reduced milk and several abnormalities in the mammary gland. This study aimed to report an outbreak of gangrenous mastitis caused by multidrug-resistant Staphylococcus haemolyticus in a Santa Inês sheep herd. Eighteen sheep were affected, and five of them with severe clinical pictures were examined. The clinical and pathological picture were variable and characterized by apathy, anorexia, emaciation, opaque and brittle hair, apparent and congested episcleral vessels, and hyperthermia. These ewes had enlarged, firm, and painful mammary glands. Macroscopically, these lesions consisted of severe gangrenous mastitis, and microscopically, the primary lesions consisted of necrosis, thrombosis, and fibrosis of the mammary parenchyma. Milk samples from one of the five severely affected ewes were collected and cultured under aerobic or microaerophilic incubation at 37°C for 24 hours on sheep blood agar. The obtained colonies were then submitted to MALDI-TOF for speciation. The colonies were also submitted to an antimicrobial susceptibility test, genotyping of virulence factors and resistance genes were also performed. The isolates showed antimicrobial multiresistance since they were resistant to seven out of 13 tested antibiotics. The isolates were also positive for two staphylococcal enterotoxigenic genes (sec and see) and fibronectin-binding protein B (fnbB).